Remarkable response to Rituximab in a 72-year-old patient with refractory non-Hodgkin's lymphoma and marrow aplasia - Egerer, Gerlinde; Sauerland, Katrin; Ho, Anthony Dick (Leukemia and lymphoma, 2001)
The chimeric human mouse antibody rituximab represents a substantial advance over the use of unmodified murine antibodies. Multicenter trials showed that rituximab induced remission in 48% of 166 relapsed lymphoma patients with minimal toxicity. Thus, the antibody might play a role in patients who cannot tolerate chemotherapy because of marrow aplasia. We observed a continuous complete remission induced by rituximab alone in a 72 year old patients with refractory and progressive high-grade non-Hodgkin's lymphoma (NHL) in the phase of chemotherapy induced marrow aplasia.